2002
DOI: 10.1002/1521-3951(200201)229:1<361::aid-pssb361>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Electrical Conductivity in Cu-Doped ZnS

Abstract: High temperature electrical conductivity (HTEC) was measured and high temperature defect equilibrium (HTDE) was analysed in ZnS:Cu to study the conditions for making p‐type material. In the high zinc vapour pressure (pZn) region, the Cu solubility limit determines the composition of phases coexisting with ZnS crystal. The negative slope of the HTEC isotherm in this region is caused by the chemical outdiffusion of Cu. The high pZn and the high sulfur vapour pressure (p italicS 2) regions are characterized by do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The diffusion of Cu into the ZnS lattice is supposed to be governed by interstitial and substitutional mechanisms. [123][124][125] It was confirmed that the ion exchange mechanism of Zn 2+ by Cu 2+ occurs on the surface, followed by a redox reaction of the adsorbed Cu 2+ into Cu + and S 2À into S À , which leads to the formation of a Cu(I)-sulfide layer on the sphalerite surface. 126 Moreover, it was found that the copper uptake was lower in the presence of oxygen.…”
Section: Materials Advancesmentioning
confidence: 84%
“…The diffusion of Cu into the ZnS lattice is supposed to be governed by interstitial and substitutional mechanisms. [123][124][125] It was confirmed that the ion exchange mechanism of Zn 2+ by Cu 2+ occurs on the surface, followed by a redox reaction of the adsorbed Cu 2+ into Cu + and S 2À into S À , which leads to the formation of a Cu(I)-sulfide layer on the sphalerite surface. 126 Moreover, it was found that the copper uptake was lower in the presence of oxygen.…”
Section: Materials Advancesmentioning
confidence: 84%
“…During the past five decades, a great deal of effort has been spent in investigating the nature of centers responsible for various kinds of luminescence in Cu-doped ZnS crystal [23][24][25][26]. In these studies, it has been gradually revealed that some native lattice defects, background or doped impurities and association of them seem to play very important roles in the luminescence characteristics of these crystals.…”
Section: Article In Pressmentioning
confidence: 99%
“…The best way to describe HTDE is to calculate defect concentrations 1 using experimentally determined HTEC isotherms and isobars data. Our study of ZnS:Cu has been in progress for many years 2–4. In our earlier works, we investigated HTEC and Cu solubility in Cu‐doped ZnS under zinc vapour pressure ( p Zn ) and under sulphur vapour pressure $(p_{{\rm S}_2 } )$ .…”
Section: Introductionmentioning
confidence: 99%